Hadith #4956 - Sahih Muslim - Rafi' bin 'Amr al-Mazni (Sahih Muslim)
Allah’s Messenger, we are going to encounter the enemy tomorrow, but we have no knives with us. Thereupon Allah’s Messenger (ﷺ) said: Make haste or be careful (in making arrangements for procuring knives) which would let the blood flow (and along with it) the name of Allah is also to be recited. Then eat, but not the tooth or nail. And I am going to tell you why it is not permissible to slaughter the animal with the help of tooth and bone; and as for the nail. it is a bone, and the bone is
Grade: Sahih

Hadith #1284 - Jami' al-Tirmidhi - al-Fadl bin Musa al-Synany الفضل بن موسى السيناني; Rafi' bin 'Amr al-Mazni (Jami' al-Tirmidhi)
“The Messenger of Allah (ﷺ) was cupped. Abu Talhah did the cupping. So he ordered that he be given two Sa’ of food, and he spoke to his masters to reduce his taxes. He said: ‘The most virtuous of what you treat with is cupping.’ Or, he said: ‘The best of your treatments is cupping.'” There are narrations on this topic from ‘Ali, Ibn ‘Abbas, and Ibn ‘Umar. The Hadith of Anas is a Hasan Sahih. Some of the people of knowledge among the Companions of the Prophet (ﷺ), and othe
Grade:

Hadith #3581 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Mshm'l bin Iyas مشمعل بن إياس; Muhammad bin Bashar Bindar محمد بن بشار بندار; Rafi' bin 'Amr al-Mazni (Sunan Ibn Majah)
the Messenger of Allah (saas) said to a man: “What do you say during your prayer?” He said: “I recite the Tashah-hud then I ask for Allah for Paradise and see refuge with Him from Hell, but by Allah I do not understand your whispering or the whispering of Mu’adh.” He said: “It is concerning them (Paradise and Hell) that we are whispering.”
Grade: